English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve.
sqrt(48 - 2y) = y

2006-12-10 04:19:45 · 8 answers · asked by badmf777 1 in Science & Mathematics Mathematics

8 answers

squaring both sides
48-2y=y^2
=>y^2+2y-48=0
=>(y+8)(y-6)=0
=>y=-8 or +6
sub y=-8
rt of 64=-8 checks
suby=+6
rt of 36=6 checks

2006-12-10 04:25:28 · answer #1 · answered by raj 7 · 0 0

sqrt(48 - 2y) = y

Your first step would be to square both sides, effectively eliminating the square root.

48 - 2y = y^2

Now, bring everything over to one side.

0 = y^2 + 2y - 48

And then we factor

(y - 6)(y + 8) = 0

Yielding the results y = -8 and y = 6

BUT WAIT! We can't assume both values work, because sometimes squaring both sides of an equation adds solutions. As an example, take this one:

x = 1

Square both sides, and you get

x^2 = 1

If we were to solve that, we'd then get:

x^2 - 1 = 0, yielding (x-1)(x+1) = 0, so x = 1 and x = -1.
As you can see, we started at x = 1 and ended up with two solutions. For that reason, we definitely have to check our solutions.

Test y = 6:
sqrt (48 - 2(6)) = 6?
sqrt(48 - 12) = 6?
sqrt(36) = 6?
This is true, for y = 6 checks out.

Test y = -8
sqrt(48 - 2(-8)) = -8?
sqrt(48 + 16) = -8?
sqrt(64) = -8?
This is false, because sqrt(64) means the "positive" square root. y = -8 fails.

Therefore, y = 6

2006-12-10 04:26:49 · answer #2 · answered by Puggy 7 · 1 0

Sqrt(48 - 2y) = y

Square both side,
48-2y = y^2

Arrange to general form,
y^2+2y-48=0

Factorise,
(y+8)(y-6)=0

y+8=0 or y-6=0
y= -8 or y=6

2006-12-10 05:21:33 · answer #3 · answered by Ranna Renni 2 · 0 0

y^2 + 2y - 48 = 0
(y-6) (y+8) = 0
y = 6 or -8

2006-12-10 04:23:04 · answer #4 · answered by NeedHelpGivesHelp 2 · 0 0

y= 6

2006-12-10 04:29:10 · answer #5 · answered by Anonymous · 0 0

Square both sides.
48-2y = y squared

Isolate a term

48 = y squared + 2Y

Um, y is 6 :)

2006-12-10 04:25:14 · answer #6 · answered by Anonymous · 0 0

sqrt(48-2y)=y / ^2
48-2y=y^2
y^2+2y-48=0
y1,2=(-2+/-sqrt(4-4*(-48))/2=-1 +/- 7
y1=6
y2=-8 false answer (y=>0 because sqrt(anything)>=0)
check:
sqrt(48-2*6)=6
sqrt(36)=6 true

2006-12-10 04:26:24 · answer #7 · answered by mashkas 3 · 0 0

(48 - 2y)^¹/2 = y
(48 - 2y) = y²
y² + 2y - 48 = 0
(y-6)(y+8) = 0

y' = -8
y'' = 6

2006-12-10 04:23:05 · answer #8 · answered by Luiz S 7 · 0 0

fedest.com, questions and answers